Determination of the Distribution of Acrylic Comonomers in Free Radicals Polymers - Andoni, Adelaida; J. Michels, Jasper; Kokalari (Teli), Efrosini; Taraj, Krenaida; Çomo, Armand (Asian Journal of Chemistry, 2012)
Some acrylate monomers have been synthesized and copolymerized by means of free radical polymerization with methyl methacrylate and butyl methacrylate. These monomers are known to introduce the desired functionality and tune the properties of the resulting polymer. The synthesized monomers and the polymers have been characterized with NMR spectroscopy. The latter is utilized to study the polymer composition and verify the distribution of the monomers in the copolymer chain. The reactivity ratios have been estimated and concluded moderately random distribution of the monomers in the copolymer chain.